Serum pre-albumin, a novel indicator of risk of anastomotic leak in bowel anastomosis - D., Sameer M.; Chase, Suchita; S., Beulah Roopavathana; Nadarajan, Abinaya R.; Nayak, Sukria (International Surgery Journal, 2018)
Background: Various preoperative and intraoperative risk factors associated with anastomotic leak have been extensively analyzed. Albumin is considered as the gold standard preoperative marker of nutrition, but recently pre-albumin is found to be a better indicator of nutrition. The main aim of this study was to analyze the preoperative risk factors including pre-albumin to predict anastomotic leak following small and large bowel anastomsois. Methods: This was a prospective observational, quality improvement study in a cohort of 100 patients undergoing small and large bowel resection in the Division of Surgery at Christian Medical College, Vellore. Univariate and multivariate analysis was done to show the significant variables associated with anastomotic leak. Results: In present study, leak rate was 21% (21/100). In univariate analysis, 6 factors had significant association with anastomotic leak, age >45 years, ASA score of II, hemoglobin ≤9.0 gm/dl, serum albumin ≤3.0 gm/dl, serum pre-albumin ≤20 mg/dl and preoperative diagnosis of malignancy. Age >45 years, ASA score of II, serum pre-albumin ≤20 mg/dl and malignancy were found to be independent risk factors of anastomotic leak. In present study prelbumin, was found to be a better indicator of anastomotic leak when compared to albumin and it was statistically significant (p=0.002). Conclusions: Serum pre-albumin is superior to albumin as an acute marker of malnutrition and help us to identify those at risk of anastomotic leak and adequately build nutrition preoperatively and decrease the morbidity.